2014
DOI: 10.1124/jpet.114.215970
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Transporter- and Enzyme-Mediated Clinical Drug-Drug Interactions of Organic Anion-Transporting Polypeptide 1B1 Substrates Using a Mechanistic Net-Effect Model

Abstract: Quantitative prediction of complex drug-drug interactions (DDIs) involving hepatic transporters and cytochromes P450 (P450s) is challenging. We evaluated the extent of DDIs of nine victim drugs-which are substrates to organic anion-transporting polypeptide 1B1 and undergo P450 metabolism or biliary elimination-caused by five perpetrator drugs, using in vitro data and the proposed extended net-effect model. Hepatobiliary transport and metabolic clearance estimates were obtained from in vitro studies. Of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 50 publications
(74 reference statements)
12
92
0
Order By: Relevance
“…Similarly, Kusuhara and Sugiyama (7) and Yoshikado et al (15, 16) describe a PBPK extended clearance model with 5 consecutive in-series liver compartments where each liver compartment mimics the dispersion model. However, as shown here, and as recognized by Pang, Caminesch, Varma, Unadkat, Riley and their co-workers (5, 914, 17, 20, 22), the extended clearance relationship is derived from the well-stirred model. Nevertheless, the dispersion clearance approach appears to be universally used to model organ clearance as described throughout the PBPK literature.…”
Section: Resultsmentioning
confidence: 56%
“…Similarly, Kusuhara and Sugiyama (7) and Yoshikado et al (15, 16) describe a PBPK extended clearance model with 5 consecutive in-series liver compartments where each liver compartment mimics the dispersion model. However, as shown here, and as recognized by Pang, Caminesch, Varma, Unadkat, Riley and their co-workers (5, 914, 17, 20, 22), the extended clearance relationship is derived from the well-stirred model. Nevertheless, the dispersion clearance approach appears to be universally used to model organ clearance as described throughout the PBPK literature.…”
Section: Resultsmentioning
confidence: 56%
“…For instance, Watanabe et al showed that the in vitro uptake clearance obtained using human hepatocytes was similar to in vivo hepatic clearance for several statins, suggesting that hepatic uptake is the rate‐determining process for the clearance of these drugs . Similar conclusions were also reported by others . Camenish and Umehara used suspended hepatocytes, liver microsomes, and sandwich‐cultured hepatocytes to estimate the intrinsic sinusoidal uptake and efflux, metabolism, and biliary secretory clearances and showed a good in vitro–in vivo extrapolation of human clearance for 13 selected compounds .…”
Section: Transporter‐mediated Disposition: Pharmacokinetics Predictionssupporting
confidence: 54%
“…The major difference between this dataset and what is reported by Lombardo et al [89] is the addition of hepatic uptake as a rate-determining process of clearance [90]. Hepatic uptake was assigned as the primary clearance mechanism through the direct availability of transporter data, or from clinical drugdrug interactions and pharmacogenomic data [7,27,[90][91][92].…”
Section: Renalmentioning
confidence: 97%
“…3b). This predominant clearance mechanism increases the reliance of Class 1B compounds on human in vitro systems such as suspension hepatocytes and sandwich culture human hepatocyte (SCHH) for predicting active hepatic uptake mediated clearance [27,49,91,[160][161][162][163][164]. In vitro tools aligned with predicting the metabolic components of drug elimination, such as human liver microsomes, will underestimate systemic clearance, although they can be critical for modelling liver concentrations [91,165].…”
Section: Class 1bmentioning
confidence: 99%